2022
DOI: 10.3390/ijms23105763
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Related to NLRP3 Inflammasome Activation Induced by Gold Nanorods

Abstract: The widespread and increasing use of engineered nanomaterials (ENM) increases the risk of human exposure, generating concern that ENM may provoke adverse health effects. In this respect, their physicochemical characteristics are critical. The immune system may respond to ENM through inflammatory reactions. The NLRP3 inflammasome responds to a wide range of ENM, and its activation is associated with various inflammatory diseases. Recently, anisotropic ENM have become of increasing interest, but knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Results showed elevated IL-1β and TNF-α levels in rats injected with OA, and rats injected with OA followed by AuNP treatment (OA-AuNP group). The correlation between AuNP treatment and increased IL-1β was investigated in a 2022 study [30]. The study found that gold nanorods induced NLRP3 inflammasome pathway activation, which involves the production of the active protease caspase-1 and cleavage of pro-IL-1β to produce bioactive IL-1β.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Results showed elevated IL-1β and TNF-α levels in rats injected with OA, and rats injected with OA followed by AuNP treatment (OA-AuNP group). The correlation between AuNP treatment and increased IL-1β was investigated in a 2022 study [30]. The study found that gold nanorods induced NLRP3 inflammasome pathway activation, which involves the production of the active protease caspase-1 and cleavage of pro-IL-1β to produce bioactive IL-1β.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%